PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN PROBLEM POSING UNTUK MENINGKATKAN KEMAMPUAN PENALARAN DAN KEMANDIRIAN BELAJAR MATEMATIKA - Hermina Amul; Nur R. Adawiyah Mahmud; Uke Ralmugiz (MEGA: Jurnal Pendidikan Matematika, 2021)
Abstract Development of Mathematics Learning Tools with Problem Posing Approach to Improve Reasoning Ability and Independence Learning Mathematics. Essay. Mathematics Education Study Program FKIP Muhammadiyah University Kupang. This study aims to develope learning tools with a problem posing approach to improve reasoning skills and independent learning mathematics. The research used is development research with the modified 4-D Models wich include the defining stage, the design stage and the develop. The population in this study were all students of class X SMA Negeri 5 Kupang. The sample in this study were students of class X of SMA Negeri 5 Kupang. Data analysis techniques used in this study to test the validity, the practicality and the effetiveness. The results showed that the learning tools in the form of RPP and LKS that have been analyzed reach very valid categories with an average score of 4,42. While the average percentage of practicality of data reached 81,67% in the good category. The effetiveness of the data obtained by the results of tests of reasoning ability and learning independence questionnaire, obtained from each student each scored 87,5% and 70% namely in the good and sufficient categories. From the results of the analysis, it was concluded that the development of mathematics learning tools with problem posing approach to improve the reasoning ability and independence of learning mathematics was feasible to use.